Education, values ​​and human rights in times of neoliberalism - Morales Basadre, Ricardo (2000)
One of the most disturbing questions at the end of the century is "what education do we need today?", but not only that, but "what education?", "for what model of development?", because education is not unrelated of the entire political, economic and social dimension of our countries. I believe that a truly urgent task is to reflect from education on this development that is beginning to have very specific characteristics in this part of America. The development of our countries in recent decades has been bumpy.